Rancang Bangun Sistem Informasi Pengelolaan Dan Pemesanan Vendor Irsada Event Grup Berbasis Website Menggunakan Model Prototype - Rahmat Dwi Maulana; Rahmi Rizkiana Putri (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2026)
The development of information technology has increased the need for digitalization in services for event organizers and vendors. Irsada Event Group, a provider of event equipment in Lamongan, previously relied on a manual system, which often caused problems such as unstructured data recording, risk of data loss, and delays in service. This study aims to develop a web-based information system for vendor management and ordering to improve operational efficiency. The system was developed using the prototype model, allowing direct collaboration with users during the design and testing stages. Laravel 11 was used as the framework, supported by a PostgreSQL database. The system offers core features such as login, registration, product ordering, payment confirmation, product management, and customer reviews. Evaluation was conducted using Black Box Testing and the System Usability Scale (SUS), resulting in 77%, indicating that the system is in the “good” category. The system supports Irsada Event Group deliver faster services and simplify digital data management.Keywords: Information Technology, event organizer vendor, website, Prototype Model, online ordering, System Usability Scale (SUS